Is open source GIS feasible in military operations? Evaluation by applying a use case - Henrico, Susan; Coetzee, Serena; Cooper, Antony (Scientia Militaria - South African Journal of Military Studies, 2020)
The study of terrain and all its related elements and facets are of crucial importance to the military. Lodi, Smit, and Ayirebi agreed with this statement and added that the importance of terrain was recognised by military leaders more than two thousand years ago.[i] Military operations can occur at any of the three levels of war: tactical, operational and strategic and can be a combat operation or a military operation other than war (MOOTW). Information about the geography empowers a military commander to plan and execute a mission successfully. As technology developed and evolved, geographic information systems (GIS) have come to play a major role in this. Today, a military operation without the use of GIS is unthinkable. In a developing country like the South Africa, however, licenses for proprietary GIS software, vendor-exclusive training and the bureaucracy of the procurement cycle add to the time and costs of a mission. The question arises whether open source software is a feasible alternative. Since the South African National Defence Force was initially trained in the use of proprietary software and it therefore became a strong habit, the perception now exits that FOSSGIS products are neither mature enough nor user-friendly enough to be used in military operations. This study evaluates the use of an open source desktop GIS product, QGIS, in a use case for a military operation “other than war” (MOOTW). QGIS outputs were compared to those produced in ArcGIS, a proprietary desktop GIS product widely used in military operations. The user-friendliness of the two products as well as pricing was also compared. Results show that the QGIS outputs provide the operational commander with equivalent information to successfully plan and execute a mission. This implies that open source GIS is suitable for military operations, especially those with limited budgets and at short notice, such as in the case of disaster relief. [i] Lodi, K., Smit, H. & Ayirebi, G. (2014). Terrain analysis in the course curricula of the South African Army Engineer Corps. Scientia Militaria: South African Journal of Military Studies, 42, 102-121.